Pemanfaatan Pojok Baca Digital Sebagai Sarana Peningkatan Literasi Digital di Dinas Perpustakaan dan Kearsipan Kota Batu - Dicky Mahendra Pangestu; Arin Prajawinanti (THE LIGHT : Journal of Librarianship and Information Science, 2025)
The development of digital information is entering the information era which is growing very rapidly, giving rise to many benefits and polemics in society, a very important ability to have is digital literacy, one of the efforts to increase digital literacy in society carried out by libraries is through the Digital Reading Corner innovation which is expected to be used to improve people's digital literacy skills. The research aims to determine the use of Digital Reading Corners as a means of increasing digital literacy in the Batu City Library and Archives Service. This research uses descriptive qualitative research methods with a grounded theory study approach. Data collection consists of observations and in-depth interviews with Digital Reading Pojok users. The data obtained was then analyzed using interactive data analysis techniques, namely data reduction, data presentation, and concluding. The results of the research show that the use of Digital Reading Corners in Batu City is quite good, but still needs to be improved, shown by the user's ability to master four elements of digital literacy skills, namely basic digital literacy skills, background information knowledge, main competencies in the field of ICT, attitudes and user perspective.